Performance of elementary school teachers on the test in elementary school science - Phonwit, Kirdmee (1979)
This study aimed to find out the performance of elementary school science teachers on the Test in Elementary School Science (TESS) which was developed by the University of the Philippines Science Education Center. The teachers' performance on the test was then related to their age, teaching experience, grade level taught, and graduate units earned